Spatial Distribution of Domestic Violence in Kermanshah City - zhila ghazvineh; bagher saroukhani; Alieh shekarbigi (جغرافیا و پایداری محیط)
Social approach has always been the dominant consideration in the study of domestic violence factors, while, this phenomenon requires a multi-dimensional investigation. This research studies the spatial distribution of domestic violence in Kermanshah. Firstly, using the lived experience, the types of marriage were identified and defined. Then, Delphi method was used by experts to collect votes in the context of their obsolete or customary nature. Due to the differences in some of the species' obsolete species, another method was used. A Grounded Theory was used. In the fourth step, using the survey method, violence was measured at three levels of psychological, verbal and physical relationships among different types of marriage. At this stage, using three methods of Balance Acceptation g, clustering and inverse sampling, 90 points of the city were selected non-randomly, non-residential areas were removed and the questionnaires were completed in 25 residential areas. The ability to explain the samples was achieved with the aim of collecting all available samples at any point by completing at least 15 and a maximum of 20 questionnaires at each point, and a total of 433 completed questionnaires were completed. The results indicate that the highest rate is concentrated among the poor and slum areas of the city. High levels of unemployment and low income, migration and the spread of marginalization, which are widespread in urban poor areas, have had a direct impact on violence. A significant part of the prevalence of some forms of cohabitation is economic poverty and cultural poverty, which directly affects urban areas. Extended Abstract 1-Introduction Domestic violence is a problem for all societies today, including modern societies. Hersberger (1996: 76) and Tennyson (2004: 98) posed domestic violence as a problem that the victims did not express; So that women consider it a taboo and they usually do not talk about it. In all countries, the cost of domestic violence is high on a yearly basis(Dejman, 1385; Moeinian, 1391; Goldfarb,2002: 63; Duvvury & et al, 2012 , 2013; Barreda & et al, 2013: 14; Darko & Walker, 2015 ; George& Bridget, 2014 : 37). The cconsequences of ddomestic vviolence always affect all family members. A great deal of research has been done on the relationship between various factors and violence, regardless of environmental and geographical factors; The predominant approach of these studies is sociological and psychological studies, and they have been neglected to study it from other valleys. Therefore, studies related to environmental or geographical factors are very rare. The present study seeks to study domestic violence with an environmental and geographical approach to demonstrate how urban slum neighborhoods, as the origin of poor economic strata, are more likely to have domestic violence than other urban neighborhoods. Understanding domestic violence with this approach will be effective in urban and social planning - in order to reduce the effects of this harmful phenomenon. 2-Materials and Methods First, using the experience of life, common species were identified, and a term was chosen for them. In the second step, which was done based on Delphi method; the participants were analyzed about the custom and unaccustomed of those four levels by a number of mostly native experts. In the third step regarding the disagreements on the obsolete species of some species such as satisfactory exchange marriages (with less severity of discrepancy) and imposed compulsory marriage (with more severity of difference, grounded theory was used to ensure conventional species. According to pervious six stages three different era (high, middle and low) of Kermanshah were selected with different social, economic and cultural characteristics. At this stage, in addition to proving the prevalence of existing species, another species was identified, which was called inevitable marriages based on its characteristics. In step four, the degree of violence was tested in different types of marriage by the Survey methods. Accordingly, a new sampling method that combines three methods of sampling is used: 1-BAS[1] sampling method that selects from all parts of the city. The second approach is somewhat similar to cluster sampling, and it considers a cluster of neighboring households for each point of the BAS and places them in the sample. The Third method is the inverse sampling method. In Inverse Sampling, sample selection continues until a certain condition is established. In this research, the two previous methods are repeated as long as the predetermined number of each of the 10 types of conjugation in the sample. Therefore, 90 points from the city of Kermanshah have been selected by non-probability sampling. The points were removed from non-residential areas and eventually 25 residential locations were selected. Point selection from point to point in the city has been done by circular method to observe the characteristics of the species and collect sample from each species in different parts of the city. Ability to explain samples by completing at least 15 and at most 20 questionnaires at each point and among women with a marriage duration of 2 to 5 years, without age limitations, and a total of 433 questionnaires have been completed. In this research, domestic violence was measured at the psychological, verbal and physical levels. Economic violence was eliminated during the pre-test phase. 3-Results and Discussion To analyze the independent variable of residential neighborhood on the dependent variable of violence, the hypothesis "psychological, verbal and physical violence varies according to the neighborhoods" and one-way ANOVA have been used for its relationship. The sig (0/000) at a significant level of 99% indicates that the residential area has a significant effect on the incidence of violence. A look at the dispersion maps of violence shows that the focus of domestic violence (in terms of psychological, verbal and physical violence) is on the poor and marginal areas of the city. The factors associated with violence in these neighborhoods include high levels of unemployment, economic poverty, low income, cultural poverty, immigration and the spread of marginalization. The dominant marriages in this area are traditional, for economic reasons, and hope to get rid of the hardships of life or with more parents' decision-making power. The focus of violence is on two points in urban good spots because of their marriage types, which are often emotional marriages, without parental consent, solely on the basis of the decision of the girl and the boy. 4-Conclusion The reduction of domestic violence, first of all, requires planning for employment, such as the development of border markets and native capacity for self-employment. Employment planning should be multiple in order to prevent the spread of some types of cohabitation, such as inevitable. In this regard, vocational training skills will help the girls of the poor and unprofitable families to contribute to their economic independence. On the other hand, the prevalence of emotional forms, which is due to extremes in strolling and the creation of temporary street friendships, the frustration of the future, and the lack of motivation for future planning and, as a result, spending time with flamboyant work should be prevented. It is believed that disappointment toward future and lack of motivation for future planning and as a result of spending time with roaming has led to the development of such behaviors. Part of planning for employment involves building infrastructure in villages, supporting seasonal workers, and promoting social welfare in order to prevent massive immigration to the city. On the other hand, poor neighborhoods need the plan for the benefit of urban amenities to preserve beauty and vitality, so that social justice can be applied in all parts of the country in relative terms. Activities in the field of informing the younger generation about desirable marriages with individual and family decisions and in order to reduce emotional marriages) and government support, the efforts of civil society activists and planning to reduce some traditional marriages are also appropriate for effective ways of marriage.